Developments and advances in defense and security : proceedings of the Multidisciplinary International Conference of Research Applied to Defense and Security (MICRADS 2018) /: proceedings of the Multidisciplinary International Conference of Research Applied to Defense and Security (MICRADS 2018). (2018) - Unknown
No abstract available